2015
DOI: 10.1021/acs.jproteome.5b00420
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Tissue Proteomics Analysis Reveals Versican as Potential Biomarker for Early-Stage Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive tumors, and the treatment outcome of this disease is improved when the cancer is diagnosed at an early stage. This requires biomarkers allowing an accurate and early tumor diagnosis. To identify potential markers for such applications, we analyzed a patient cohort consisting of 50 patients (50 HCC and 50 adjacent nontumorous tissue samples as controls) using two independent proteomics approaches. We performed label-free discovery analysis on 19 HCC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 47 publications
2
46
0
1
Order By: Relevance
“…Reptin has been consistently shown overexpressed in human HCC [2, 3133] where a high level of expression is correlated with a poor prognosis [2]. We and others have shown that Reptin is a potent mediator of oncogenesis and is considered as an attractive target in cancer [2, 3, 57, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Reptin has been consistently shown overexpressed in human HCC [2, 3133] where a high level of expression is correlated with a poor prognosis [2]. We and others have shown that Reptin is a potent mediator of oncogenesis and is considered as an attractive target in cancer [2, 3, 57, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Taleb et al elegantly performed a quantitative proteome analysis of plasma MVs in patients with HCV‐induced cirrhosis which revealed that versican core protein (VCAN) was abundant in cirrhotic patients with a further increase in HCC. VCAN is an extracellular matrix component that has been linked to various types of cancer . VCAN is also known to interact with Hyaluronan which has been proposed as a non‐invasive biomarker for liver fibrosis and cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Naboulsi et al . demonstrated that versican core protein (VCAN) is a potential biomarker for early HCC diagnosis by label-free discovery analysis: selected (multiple) reaction monitoring (SRM/MRM)20. It was also reported that protein S100A9, which was dramatically up-regulated in sera from HCC patients, is a candidate HCC diagnostic biomarker21.…”
Section: Discussionmentioning
confidence: 99%